UPAYA MENINGKATKAN HASIL BELAJAR PASSING BAWAH BOLA VOLI MELALUI VARIASI MEDIA PEMBELAJARAN KEDINDING PADA SISWA KELAS V SD NEGERI 25/ IV KOTA JAMBI - Eka Widya Purwaningsih; Alex Oktadinata; Iwan Budi Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This classroom action research aimed to improve learning outcomes in underhand volleyball passing through the use of wall-based learning media among fifth-grade students of SD Negeri 25/IV Kota Jambi. The research employed a collaborative approach with classroom teachers using the Kemmis and Taggart model, consisting of planning, action, observation, and reflection stages. The research was conducted in two cycles, each comprising three meetings. Data were collected through observation, tests, and documentation, then analyzed both qualitatively and quantitatively. In the pre-cycle stage, only 30% of students achieved the minimum learning mastery standard (KKM ≥75). After implementing the wall media variation, there was a gradual improvement. In Cycle I, student mastery rose to 45%, and in Cycle II, it significantly increased to 85%. Student activity and engagement also improved in each cycle. The results indicated that using varied wall-based learning media effectively enhanced students’ technical performance in underhand volleyball passing. Thus, the study concludes that the application of wall-based media in physical education can positively impact students’ cognitive and motor skill development in volleyball.